Fasting Ramadan During COVID-19 Pandemic: Immunomodulatory Effect - Abunada, Taghreed; Abunada, Hanan; Zayed, Hatem (Frontiers in Nutrition, 2020)
As of April 24, 2020, more than 1.6 billion Muslims observe the holy fasting month of Ramadan worldwide. The safety of fasting of healthy adult Muslims during the COVID-19 era is debatable. In this perspective, we discuss the available scientific evidence of the advantages of fasting against COVID-19.